Az Észak-alföldi Régióban végzett teljesítménymenedzsment-vizsgálat egy módszerének ismertetése a verseny- és közszférában - Gergely, Éva (Közép-Európai Közlemények, 2011)
I carry out my research within the research program “Functional Investigation of Enterprise Management” constructed by the Institute of Management and Organization in the University of Debrecen, Centre for Agricultural and Applied Economic Sciences, Faculty of Applied Economics and Rural Development. The research topic consists of three bigger subtopics, such as Investigation of Organization Management, Investigation of Human Resource Management and Investigation of Process Management. The research field of investigating performance management belongs to the Investigation of Human Resource Management. I have been investigating the system of performance management for six years; I have been using the finalized formal questionnaire constructed for the structural data collection, worked over for several times for three years. By the help of questionnaires limited companies and local governments are examined relating to the similarities and differences of the two spheres in connection with the system of performance evaluation. The questionnaire contains the following comprehensive fields: •Evaluating the importance of performance management among the other HRM functions, •Methods of performance management used, •Aims of performance evaluation, •Aspects and competences to be evaluated during performance evaluation, •Measuring the expected performance objectives, •Factors causing the biggest problems during performance evaluation, detectable mistakes in the systems of performance management. The aim of this study is to detail the content of the questionnaire and the examined issues. I am going to introduce the questionnaire, which was constructed by me, and is used in my research for examining performance evaluation, and to detail the structure and the content of the questionnaire.